2013
DOI: 10.1089/ast.2012.0817
|View full text |Cite
|
Sign up to set email alerts
|

Abiotic Production of Methane in Terrestrial Planets

Abstract: On Earth, methane is produced mainly by life, and it has been proposed that, under certain conditions, methane detected in an exoplanetary spectrum may be considered a biosignature. Here, we estimate how much methane may be produced in hydrothermal vent systems by serpentinization, its main geological source, using the kinetic properties of the main reactions involved in methane production by serpentinization. Hydrogen production by serpentinization was calculated as a function of the available FeO in the crus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(62 citation statements)
references
References 61 publications
(72 reference statements)
2
60
0
Order By: Relevance
“…Kasting and Brown (1998) estimate a methane abundance of 0.5 ppm (mixing ratio of 5×10 −7 ) for a 1-bar N 2 -CO 2 atmosphere assuming conversion of 1% carbon flux from mid-ocean ridges to CH 4 prior to the rise of life. Kasting (2014) echo this estimated mixing ratio for a CH 4 source of serpentinization of ultramafic rock with seawater at present-day levels, while Guzmán-Marmolejo et al (2013) estimate serpentinization can drive CH 4 levels up to 2.1 ppmv. However, Kasting (2014) also note that methane production from impacts could have outpaced the supply from serpentinization multiple orders of magnitude, and could have sustained abiotic CH 4 levels up to 1000 ppmv.…”
Section: Alternate Shielding Gasesmentioning
confidence: 65%
“…Kasting and Brown (1998) estimate a methane abundance of 0.5 ppm (mixing ratio of 5×10 −7 ) for a 1-bar N 2 -CO 2 atmosphere assuming conversion of 1% carbon flux from mid-ocean ridges to CH 4 prior to the rise of life. Kasting (2014) echo this estimated mixing ratio for a CH 4 source of serpentinization of ultramafic rock with seawater at present-day levels, while Guzmán-Marmolejo et al (2013) estimate serpentinization can drive CH 4 levels up to 2.1 ppmv. However, Kasting (2014) also note that methane production from impacts could have outpaced the supply from serpentinization multiple orders of magnitude, and could have sustained abiotic CH 4 levels up to 1000 ppmv.…”
Section: Alternate Shielding Gasesmentioning
confidence: 65%
“…, on extremely cold worlds like Titan with reducing atmospheres), on a planet like Archean Earth, the presence of hydrocarbon haze may require a higher level of methane production than is possible from abiotic sources alone. The maximum abiotic methane production rate from serpentinization, its primary nonbiological source, has been estimated as 6.8 × 10 8 and 1.3 × 10 9 molecules/cm 2 /s for rocky planets of 1 and 5 Earth masses, respectively (Guzmán-Marmolejo et al , 2013), although there has been earlier speculation of higher abiotic production rates (Kasting, 2005; Shaw, 2008), especially if ancient seafloor spreading rates were faster or the amount of iron-rich ancient seafloor rock was greater. Based on their calculations, Guzmán-Marmolejo et al (2013) suggested that an atmospheric CH 4 concentration greater than 10 ppmv is suggestive of life.…”
Section: Discussionmentioning
confidence: 99%
“…The maximum abiotic methane production rate from serpentinization, its primary nonbiological source, has been estimated as 6.8 × 10 8 and 1.3 × 10 9 molecules/cm 2 /s for rocky planets of 1 and 5 Earth masses, respectively (Guzmán-Marmolejo et al , 2013), although there has been earlier speculation of higher abiotic production rates (Kasting, 2005; Shaw, 2008), especially if ancient seafloor spreading rates were faster or the amount of iron-rich ancient seafloor rock was greater. Based on their calculations, Guzmán-Marmolejo et al (2013) suggested that an atmospheric CH 4 concentration greater than 10 ppmv is suggestive of life. At the range of pCO 2 allowed by Driese et al (2011), we find that the CH 4 flux needed to initiate haze formation ranges between about 1 × 10 11 and 3 × 10 11 molecules/cm 2 /s, broadly consistent with estimates for the biological Archean methane flux after the origin of oxygenic photosynthesis (Kharecha et al , 2005; Claire et al , 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While life produces the overwhelming majority (>99%) of CH 4 in the Earth's atmosphere (Kasting 2005), some geologic processes emit small amounts of CH 4 (e.g., Etiope and Sherwood Lollar 2013). Additionally, serpentinization, the hydration of ultramafic (e.g., basaltic) seafloor, releases substantial amounts of H 2 , which can (in the presence of CO 2 ) result in CH 4 production (Guzmán-Marmolejo et al 2013;Etiope and Sherwood Lollar 2013). However, there is wide disagreement on the fraction of CH 4 from serpentinizing systems on Earth that is biological, rather than geochemical in nature; this is an important area of future work for this false-positive source.…”
Section: Revisiting Part Of the Brief List Of Biosignaturesmentioning
confidence: 99%